THE ROLE OF BORIBOY AHMEDOV RESEARCH IN TEMURID STATE IN CENTRAL ASIA (European Journal of Interdisciplinary Research and Development, 2023)
The article tried to reveal the place of research of Academician of the Academy of Sciences of Uzbekistan, honored scientist, historian and Orientalist, doctor of historical sciences Bo'riboy Ahmedov (1924-2002) in the study of the history of Amir Temur and the Timurid state.